2008
DOI: 10.1016/j.bmcl.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of substituted trans-2-arylcyclopropylamine inhibitors of the human histone demethylase LSD1 and monoamine oxidases A and B

Abstract: A facile synthetic route to substituted trans-2-arylcyclopropylamines was developed to provide access to mechanism-based inhibitors of the human flavoenzyme oxidase lysine-specific histone demethylase LSD1 and related enzyme family members such as monoamine oxidases A and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 19 publications
0
60
0
Order By: Relevance
“…11 A number of inhibitors based on the tranylcypromine scaffold have now been discovered, and in a few cases they have nanomolar IC 50 values against recombinant LSD1. 9, 1217 In 2007, we described a series of (bis)guanidines and (bis)biguanides that act as potent LSD1 inhibitors, increase H3K4 methylation and promote the re-expression of aberrantly silenced tumor suppressor genes in vitro. 8 The lead compound emerging from these studies, verlindamycin (2, Figure 1, aka 2d), is synergistic with the deoxynucleotide-N-methyltransferase (DNMT) inhibitor 5-azacytidine (5-AC) in limiting tumor growth in an HCT116 xenograft study in athymic mice, 18 and has been shown to promote the re-expression of the silenced e-cadherin gene in acute myeloid leukemia cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…11 A number of inhibitors based on the tranylcypromine scaffold have now been discovered, and in a few cases they have nanomolar IC 50 values against recombinant LSD1. 9, 1217 In 2007, we described a series of (bis)guanidines and (bis)biguanides that act as potent LSD1 inhibitors, increase H3K4 methylation and promote the re-expression of aberrantly silenced tumor suppressor genes in vitro. 8 The lead compound emerging from these studies, verlindamycin (2, Figure 1, aka 2d), is synergistic with the deoxynucleotide-N-methyltransferase (DNMT) inhibitor 5-azacytidine (5-AC) in limiting tumor growth in an HCT116 xenograft study in athymic mice, 18 and has been shown to promote the re-expression of the silenced e-cadherin gene in acute myeloid leukemia cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on LSD1 have identified several inhibitors, such as tranylcypromine, S2101, and CBB1007, which efficiently blocks LSD1-mediated demethylation of H3K4me2 [14][15][16]. H3K4me2 is an important histone mark that is frequently associated with gene activation, and recent studies using ChIP-seq data have shown that H3K4me2 has specific binding patterns on tissue-specific genes in human CD4+ T cells, neural tissues, and mouse brain tissues [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Some trans-2-PCPA analogues carrying 4-bromo, 4-methoxy, and 4-trifluoromethoxy substitutions at the benzene ring led to compounds (19)(20)(21) with similar or slightly improved activity against LSD1. 59 Interestingly, the introduction of a bulky, branched substituent at the 4 position of the benzene ring, able to occupy the wide space present in the LSD1 cavity surrounding the FAD cofactor and the AO domain, furnished tranylcypromine-based compounds such as 22-27 endowed with high potency against LSD1 and scarce or no activity against MAOs. 55,56 Compounds 22 and 23 were also reported to be active against a panel of cancer cell lines with growth inhibition 50% (GI 50 ) values ranging from 6.0 to 67 µM (Table 2), 55 whereas 26 was able to inhibit cell growth and induce differentiation in murine acute promyelocytic leukemia (APL) blasts as M Monographs a single agent and in APL-derived NB4 cells in synergy with retinoic acid (RA).…”
Section: Anti-mao-based Small Moleculesmentioning
confidence: 99%